Indirect Requests for Students of English as a Foreign Language - López MontenegRo, Rosberly (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2017)
This article provides part of the results of the investigation project B4279 “Acquisition of indirect requests in students of English as a foreign language”. This study explores the most appropriate types of requests for students of extension courses of the Project ED-2884 and the English Teaching Major, both from the Paci c Regional Campus of University of Costa Rica. The instrument for the analysis was based on Keburise (2012). It is composed of ve communicative situations with ve different requests each. The purpose of the instrument is for the students to select the ones they consider the most appropriate for each case. The research establishes the preference of interrogatives through concealed imperatives and directive requests.  El artículo informa parte de los resultados del proyecto de investigación B4279 Adquisición de peticiones indirectas en estudiantes de inglés como lengua extranjera. Dicho estudio explora los tipos de peticiones considerados más apropiados para el estudiantado de los cursos libres de inglés del proyecto de Acción Social ED-2884 y de la carrera de Enseñanza del Inglés, ambos de la Sede del Pací co de la Universidad de Costa Rica. Este análisis se realizó mediante un instrumento basado en Keburise (2012), compuesto de cinco situaciones comunicativas con cinco tipos de peticiones distintas, cada una con el n de que los sujetos del estudio elijan las que consideren más apropiadas para cada caso. La investigación señala la preferencia de fórmulas interrogativas para solicitar lo deseado, por medio de fórmulas imperativas encubiertas y peticiones directivas.